Workshop Penerapan Media Pembelajaran Menggunakan Teknologi untuk Meningkatkan Minat Belajar Siswa Sekolah Menengah Atas (SMA) di Kabupaten Padang Pariaman - Yosa Novia Dewi; Sherly Franchisca; Rona Rossa; Febriyanno Suryana; Lis Hafrida (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2021)
Interest in learning is one of the determining factors for achieving learning objectives. Through interest, students will have the urge to follow the ongoing learning process. One way to increase student interest in learning is by using technology in earning process, such as the use of technology- based learning media. Learning media that are used appropriately in the learning process will be a more effective and efficient supporting tool in achieving learning objectives. The purpose of this workshop is to increase the learning interest of Senior High School students in Padang Pariaman Regency through the use of learning media using technology. This workshop is not only intended for students but also the teachers. University Community Engagement Program (PkM) is carried out through 5 (five) stages, namely: the preliminary stage, the socialization and audience stage, the workshop implementation stage, and the final evaluation stage. The workshop is conducted for 2 (two) days and is given separately for teachers and students. On the first day, the material was presented to teachers and students. Furthermore, the second day of the workshop focused on the practice of making learning media using the internet and its use.